One-Step Calibration of AFM in Liquid - Sumbul, Fidan; Hassanpour, Nahid; Rodriguez-Ramos, Jorge; Rico, Felix (Frontiers in Physics, 2020)
Nanomechanical measurements of cells and single molecules with atomic force microscopy (AFM) require accurate calibration of two parameters: the spring constant of the cantilever (k) and the inverse of the optical lever sensitivity (InvOLS). The most established calibration approach in liquid consists in determining the InvOLS from force–distance curves on a stiff surface, k being calculated using the thermal spectrum (PSD) of the cantilever via the equipartition theorem. Recent works proposed using cantilevers with calibrated k and then determining the InvOLS from the PSD. These non-contact approaches improve the precision of nanomechanical measurements compared to conventional contact-based approaches. The Sader method or the recent global calibration initiative (GCI) are accurate approaches and do not require knowledge of the InvOLS to determine k, thus they would allow one-step calibration of AFM in liquid. However, both methods assume high quality factor cantilevers, not the case for most cantilevers in liquid. Here we assess the accuracy and precision of the Sader and GCI methods in liquid on two types of cantilevers with low Q-factor using two different PSD fitting models (SHO and Pirzer). We evaluate the two approaches using only the PSD in liquid to calibrate both k and the InvOLS. While both methods led to similar results, the GCI approach is less prone to systematic uncertainties and, using the SHO model, provides higher accuracy in k and the InvOLS. Therefore, the proposed SHO, GCI-based approach utilizing only the thermal spectrum in liquid is precise and accurate and allows one-step calibration of AFM.